Students' Acceptance of Digital Learning Tools in Programming Education Course using Technology Acceptance Model - Krittawaya Thongkoo (2020)
© 2020 IEEE. Research on the success of the integration between educational technology and pedagogy approach has widely studied over the past decades. Therefore, implementing pedagogy with innovation and new technology would create a tempting learning environment. In this study, digital learning was proposed as a distance learning environment to investigate the students' acceptance using the Technology Acceptance Model (TAM). This research explored the acceptance of the proposed digital learning of second-year students. Students were divided into two groups, an experimental group (n=25) and control group (n=25). This study also provided five indicators of students' acceptance of digital learning included: User Interface Design, Perceived Usefulness, Perceived Ease of Use, Attitude, and Intention to Use that would contribute to its successful use. The experiment results revealed that the proposed approach affected the students' acceptance effectively and promoted positive perception toward the system.